Effectiveness of Structural Systemic Training on Control Strategies Among Women With a Desire for Divorce - Riahi Far, Fataneh; Yousefi, Zahra; Golparvar , Mohsen (Mental Health and Lifestyle Journal, 2026)
This study was conducted with the aim of comparing the effectiveness of attachment-based systemic training and structural systemic training on control strategies among women with a desire for divorce. The research was an experimental study with a pre-test, post-test, and follow-up design including a control group. The research population comprised all women with a desire for divorce in the city of Isfahan in 2025. The sample consisted of 60 women with a desire for divorce who were selected via convenience sampling based on inclusion and exclusion criteria, and were randomly assigned to two experimental groups and one control group. All subjects were evaluated across three stages: pre-test, post-test, and follow-up using the research instrument. The research instrument was the Control Strategies Questionnaire (Yousefi & Bahrami, 2017). The collected data were analyzed using descriptive statistics (mean and standard deviation) and inferential statistics (repeated measures analysis of variance). The results indicated that both methods were effective on the dimensions of control strategies, and there was no significant difference between their effectiveness, except for adaptive control, where the structural systemic method had a significantly greater impact. Based on these results, it can be concluded that both methods are effective in improving the dimensions of control among women with a desire for divorce.